Prevalence of Self-Reported Spondyloarthritis Features in a Cohort of Patients with Inflammatory Bowel Disease - Carmen Stolwijk; Marieke Pierik; Robert Landewé; Ad Masclee; Astrid van Tubergen (Canadian Journal of Gastroenterology)
BACKGROUND: Musculoskeletal symptoms belonging to the spectrum of ‘seronegative spondyloarthritis’ (SpA) are the most common extraintestinal manifestations in patients with inflammatory bowel disease (IBD) and may lead to important disease burden. Patients with suspected SpA should be referred to a rheumatologist for further evaluation.